Perceived challenges affecting elderly people and their effect on their ability to obtain social protection and healthcare services In Tanzania - Ramadhan Said Naibu; Willy Maligany (Journal of Management and Science, 2025)
Ageing has been regarded as an important policy issue worldwide because of the large proportion of elderly people. Despite efforts to improve access to healthcare services, the elderly in Tanzania still face various challenges. This study was conducted to explore the challenges affecting elderly people from accessing NHIF in Kinoindoni Municipal Council. The study population comprised elderly individuals in selected wards in Kinondoni Municipal Council. A sample size of 394 elderly people was purposively sampled for the study. Data collection involved mixed-methods that combined questionnaires, in-depth interviews, document reviews, and focus group discussions to obtain the data. While the Statistical Package for Social Science was used to analyse quantitative data, content analysis was employed to analyse qualitative data. The study revealed several key challenges elderly individuals face in accessing NHIF services in Tanzania. Financial constraints emerged as the most significant barrier, with 75% of the respondents citing difficulties in affording premiums and out-of-pocket expenses, often leading them to forgo necessary healthcare. Administrative hurdles, such as complex enrolment processes and bureaucratic inefficiencies, were also prevalent, with 75% acknowledging that these obstacles impede their ability to utilize NHIF benefits effectively. Additionally, a lack of awareness regarding NHIF services was noted by 75% of participants, indicating that many elderly individuals do not fully understand their rights or available benefits. These findings highlight for the need for targeted interventions to improve accessibility and health outcomes.